AMP‐activated protein kinase regulates glycocalyx impairment and macrophage recruitment in response to low shear stress. Issue 6 (12th March 2019) - Zhang, Junjie; Kong, Xiangquan; Wang, Zhimei; Gao, Xiaofei; Ge, Zhen; Gu, Yue; Ye, Peng; Chao, Yuelin; Zhu, Linlin; Li, Xiaobo; Chen, Shaoliang
ABSTRACT: Low shear stress (LSS) increases degradation of the endothelial glycocalyx, leading to production of endothelial inflammation and atherosclerosis. However, the underlying mechanisms of how LSS diminishes the endothelial glycocalyx remain unclear. We showed that LSS inactivated AMPK, enhanced Na + ‐H + exchanger (NHE)1 activity, and induced glycocalyx degradation. Activation of AMPK prevented LSS‐induced NHE1 activity and endothelial glycocalyx impairment. We further identified hyaluronidase 2 (HYAL2) as a mediator of endothelial glycocalyx impairment in HUVECs exposed to LSS. Inactivation of AMPK by LSS up‐regulates the activity of HYAL2, which acts downstream of NHE1. We characterized a left common carotid artery partial ligation (PL) model of LSS in C57BL/6 mice. The results showed decreased expression of hyaluronan (HA) in the endothelial glycocalyx and decreased thickness of the endothelial glycocalyx in PL mice. Pharmacological activation of AMPK by ampkinone not only attenuated glycocalyx impairment due to HA degradation but also blocked vascular cell adhesion molecule 1 and intercellular adhesion molecule 1 expression increase and macrophage recruitment in the endothelia of PL mice. Our results revealed that AMPK dephosphorylation induced by LSS activates NHE1 and HYAL2 to promote HA degradation and glycocalyx injury, which may contribute to endothelial inflammatory reaction and macrophage recruitment.—Zhang, J., Kong, X., Wang, Z., Gao, X., Ge, Z., Gu, Y., Ye, P., Chao, Y., Zhu, L., Li, X., Chen, S. AMP‐activated protein kinase regulates glycocalyx impairment and macrophage recruitment in response to low shear stress. FASEB J. 33, 7202–7212 (2019). www.fasebj.org